The United Kingdom’s Coronavirus Act, deprivations of liberty, and the right to liberty and security of the person - Pugh, J (Oxford University Press, 2020)
In response to the SARS-CoV-2 coronavirus pandemic the UK government has passed the Coronavirus Act 2020 (CA). Among other things, this act extends existing statutory powers to impose restrictions of liberty for public health purposes. The extension of such powers naturally raises concerns about whether their use will be compatible with human rights law. In particular, it is unclear whether their use will fall within the public heath exception to the Article 5 right to liberty and security of the person in the European Convention of Human Rights. In this paper, I outline key features of the CA, and briefly consider how the European Court of Human Rights has interpreted the public health exception to Article 5 rights. This analysis suggests two grounds on which restrictions of liberty enforced some under the CA might be vulnerable to claims of Article 5 rights violations. First, the absence of specified time limits on certain restrictions of liberty means that they may fail the requirement of legal certainty championed by the European Court in its interpretation of the public health exception. Second, the Coronavirus Act’s extension of powers to individuals lacking public health expertise may undermine the extent to which the act will ensure that deprivations of liberty are necessary and proportionate.